Rapid preparation and performances of garnet electrolyte with sintering aids for solid-state Li–S battery. Issue 13 (1st July 2021) - Yang, Li; Huang, Xiao; Zou, Changfei; Tao, Xiyuan; Liu, Lei; Luo, Kaili; Zeng, Peng; Dai, Qiushi; Li, Yongfang; Yi, Lingguang; Luo, Zhigao; Wang, Xianyou
Abstract: Lithium-sulfur (Li–S) batteries are attractive due to their high theoretical energy density. However, conventional Li–S batteries with liquid electrolytes undergo polysulfide shuttle-effect and lithium dendrite formation during charge/discharge process, leading to poor electrochemical performance and safety issues. Garnet type Li7 La3 Zr2 O12 (LLZO) solid-state electrolyte (SSE) restricts the penetration of polysulfides and exhibits high ionic conductivity at room temperature (RT). Herein, Li6.5 La3 Zr1.5 Nb0.5 O12 (LLZNO) ceramic electrolyte using Li3 PO4 (LPO) as sintering aids (LLZNO-LPO) is prepared by the rapid sintering method and is applied to construct a shuttle-effect free solid-state Li–S battery. The SSE displays high conductive pure cubic-LLZO phase; during the rapid sintering, LPO melts and junctions the voids between the grains, thus improves Li + conductivity. As a result, the LLZNO-LPO ceramic electrolyte with Li + conductivity of 4.3 × 10 −4 S cm −1 and high critical current density (CCD) of 1.2 mA cm −2 is obtained at RT. The Li–S solid-state battery which utilizes LLZNO-LPO ceramic electrolyte can deliver an initial discharge capacity of 943 mA h·g −1 and 602 mA h·g −1 retention after 60 cycles. In the same time, the initial coulombic efficiency is as high as 99.5%, indicating that the SSE can effectively block the polysulfide shuttle towards the Li anode and fulfill a shuttle-free Li–S battery.